2004
DOI: 10.1214/105051604000000288
|View full text |Cite
|
Sign up to set email alerts
|

Random oriented trees: A model of drainage networks

Abstract: Consider the d-dimensional lattice Z d where each vertex is "open" or "closed" with probability p or 1 − p, respectively. An open vertex v is connected by an edge to the closest open vertex w such that the dth co-ordinates of v and w satisfy w(d) = v(d) − 1. In case of nonuniqueness of such a vertex w, we choose any one of the closest vertices with equal probability and independently of the other random mechanisms. It is shown that this random graph is a tree almost surely for d = 2 and 3 and it is an infinite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 13 publications
1
51
0
Order By: Relevance
“…Let H be the space of compact subsets of (Π, d Π ) equipped with the Hausdorff metric d H given by, Ferrari et al [10] have shown that, for d = 2, the random graph on the Poisson points introduced by [12], converges to a Brownian web under a suitable diffusive scaling. Coletti et al [7] have a similar result for the discrete random graph studied in Gangopadhyay et al [13]. Baccelli et al [5] have shown that scaled paths of the successive ancestors in the DSF converges weakly to the Brownian motion and also conjectured that the scaling limit of the DSF is the Brownian web.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Let H be the space of compact subsets of (Π, d Π ) equipped with the Hausdorff metric d H given by, Ferrari et al [10] have shown that, for d = 2, the random graph on the Poisson points introduced by [12], converges to a Brownian web under a suitable diffusive scaling. Coletti et al [7] have a similar result for the discrete random graph studied in Gangopadhyay et al [13]. Baccelli et al [5] have shown that scaled paths of the successive ancestors in the DSF converges weakly to the Brownian motion and also conjectured that the scaling limit of the DSF is the Brownian web.…”
Section: Introductionmentioning
confidence: 84%
“…The graph studied in [13] connected an open vertex u to the vertex h(u) with h(u) being the nearest open vertex in {w : w(d) = u(d) + 1}, with the vertex being chosen with uniform probability in case there are more than one nearest open vertex. This construction immediately leads to a Markovian analysis which is exploited in [13] to obtain the tree/forest dichotomy. However the DSF model considered here has to take care of a 'history' set arising from the paths constructed in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the image of ∂K 0 under F n forms a coalescing flow on the circle, where for x, y ∈ ∂K 0 ⊂ ∂K n , the length of the arc between F n (x) and F n (y) on the unit circle is proportional to the probability that a new particle will be attached to the corresponding part of ∂K n between x and y. In the limit that the particle radius δ ↓ 0, while time is sped up by a factor of δ −3 , this coalescing flow can be seen as a localized disturbance flow studied in [NT15], which converges to the coalescing Brownian flow on the circle Figure 19: From left to right, illustration of paths in the drainage network of [GRS04], the drainage network of [RSS16a], Poisson trees [FLT04], the directed spanning forest [BB07], and the radial spanning tree [BB07]. w.r.t.…”
Section: Planar Aggregation Modelsmentioning
confidence: 99%
“…From the construction, it follows that the random graph, G = (V, E) with edge set E := { u, h(u) : u ∈ V }, does not contain any circuit. This model has been studied by Gangopadhyay, Roy and Sarkar [10] and the following results were obtained. (i) For d = 2 and d = 3, G consists of one single tree almost surely, and for d ≥ 4, G is a forest consisting of infinitely many disjoint trees almost surely.…”
mentioning
confidence: 99%